#### Question

Solve the following quadratic equations by factorization:

`4sqrt3x^2+5x-2sqrt3=0`

#### Solution

We have been given

`4sqrt3x^2+5x-2sqrt3=0`

`4sqrt3x^2+8x-3x-2sqrt3=0`

`4x(sqrt3x+2)-sqrt3(sqrt3x+2)=0`

`(sqrt3x+2)(4x-sqrt3)=0`

Therefore,

`sqrt3x+2=0`

`sqrt3x=-2`

`x=-2/sqrt3`

or,

`4x-sqrt3=0`

`4x=sqrt3`

`xsqrt3/4`

Hence, `x=-2/sqrt3` or `xsqrt3/4`

Is there an error in this question or solution?

#### APPEARS IN

Solution Solve the Following Quadratic Equations by Factorization: `4sqrt3x^2+5x-2sqrt3=0` Concept: Solutions of Quadratic Equations by Factorization.